Cerebral microemboli during extracorporeal life support: a single-centre cohort study. (18th August 2021) - Kietaibl, Clemens; Horvat Menih, Ines; Engel, Adrian; Ullrich, Roman; Klein, Klaus U; Erdoes, Gabor
Abstract:  : OBJECTIVES: The aim of this study was to investigate the load and composition of cerebral microemboli in adult patients undergoing venoarterial extracorporeal life support (ECLS). METHODS: Adult ECLS patients were investigated for the presence of cerebral microemboli and compared to critically ill, pressure-controlled ventilated controls and healthy volunteers. Cerebral microemboli were detected in both middle cerebral arteries for 30 min using transcranial Doppler ultrasound. Neurological outcome (ischaemic stroke, global brain ischaemia, intracerebral haemorrhage, seizure, metabolic encephalopathy, sensorimotor sequelae and neuropsychiatric disorders) was additionally evaluated. RESULTS: Twenty ECLS patients (cannulations: 15 femoro-femoral, 4 femoro-subclavian, 1 femoro-aortic), 20 critically ill controls and 20 healthy volunteers were analysed. ECLS patients had statistically significantly more cerebral microemboli than critically ill controls {123 (43–547) [median (interquartile range)] vs 35 (16–74), difference: 88 [95% confidence interval (CI) 19–320], P  =   0.023} and healthy volunteers [11 (5–12), difference: 112 (95% CI 45–351), P  <   0.0001]. In ECLS patients, 96.5% (7346/7613) of cerebral microemboli were of gaseous composition, while solid cerebral microemboli [1 (0–5)] were detected in 12 out of 20 patients. ECLS patients had more neurological complications than critically ill controls (12/20 vs 3/20, P  =   0.003). In ECLS patients, a high microembolic rate (>100/30 min) tended to be associated with neurological complications including ischaemic stroke, neuropsychiatric disorders, sensorimotor sequelae and non-convulsive status epilepticus (odds ratio 4.5, 95% CI 0.46–66.62; P  =   0.559). CONCLUSIONS: Our results indicate that adult ECLS patients are continuously exposed to many gaseous and, frequently, to few solid cerebral microemboli. Prolonged cerebral microemboli formation may contribute to neurological morbidity related to ECLS treatment. Clinical trial registration: ClinicalTrials.gov, NCT02020759, https://clinicaltrials.gov/ct2/show/NCT02020759?term=erdoes&rank=1 . Abstract : Venoarterial extracorporeal life support (ECLS) is increasingly used as bridging therapy in critically ill patients with severe cardiorespiratory failure or recovering from major cardiothoracic surgery [1, 2].